Model Pengembangan Modal Sosial Adaptif Pada Komunitas Petani Kedelai Berbasis Program Upsus Pajale Di Kabupaten Lampung Timur - Septi Ana; Lucyana Trimo (Politeknik Negeri Lampung., 2019)
This study aims to design a model of adaptive social capital development in the soybean farming community based on the UPSUS Pajale Program in East Lampung Regency, which was held from January to March 2019. The data used were primary and secondary data with the Mix-method research method. The sampling technique used is Proportional Stratified Random Sampling with a total sample of 140 soybean farmers who are members of a farmer group receiving 2017 UPSUS Pajale Kedelai Program in East Lampung Regency. Data processing is done qualitatively and quantitatively. Qualitatively the data is processed using descriptive analysis, while the quantitative data is processed using Structural Equation Modeling (SEM) analysis, which uses the LISREL 8.80 program. The results showed that the soybean farmer's social capital development model obtained was an adaptive implementation model developed through strengthening the program implementation process, farmer characteristics and institutional institutional performance in supporting the sustainability of the next UPSUS Pajale Program and could also be applied to other government programs.Â Keywords: Development Model, Social Capital, and UPSUS Pajale Program